Stand strong you can overcome bullying (and other stuff that keeps you down) - Vujicic, Nick (WaterBrook Press, 2014)
With no arms, no legs, and no defense , Nick Vujicic was once a bully's target and knows what it feels like to be picked on and pushed around: It makes your stomach hurt, gives you nightmares, and feels like there is no hope in sight. But Nick shows how you too can overcome and rise above bullying. No Bully Can Define Who You Are. Nick has experienced bullying of all kinds for being "different". But he's learned that he doesn't have to play the bully's game--and neither do you. In Stand Strong Nick gives you strategies for developing a "bully defense system," so you can handle bullies of all kinds by building your strength from the inside out.